Legal Protection of Children Facing the Law for Their Published Identities - Kalsela, Wanda Frisilia; Alhadi, Muhammad Nurcholis; Prasetyo, Bayu (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The news that contains the identity of children involved in legal cases, whether as perpetrators, victims or witnesses, is a crucial issue because it can interfere with their physical, emotional and social development. Indonesian law has established various regulations that strictly prohibit the disclosure of children's identities in order to protect their rights. This research focuses on analyzing legal policies governing the protection of children in mass media coverage, particularly in the context of disclosing their identities.Purposes of the Research: In addition, the study also evaluated potential legal consequences, including criminal sanctions and possible violations of the journalistic code of ethics.Methods of the Research: Using a descriptive normative juridical method, this research explores the applicable legal provisions, the pattern of media coverage, and the impact caused by violations of these rules.Findings of the Research: The findings of the study show that although there are clear rules regarding the protection of children's identities, their implementation is still hampered by several problems, such as the lack of understanding of journalists of relevant laws and indecisiveness in sanctioning violations. This study also identifies a number of laws that regulate criminal liability against mass media, including